Let's have the first number, the larger number, be <em>x</em>. We'll have the second, smaller number be <em>y</em>.
We know that x = y + 6, since x is 6 greater than y.
We also know that 330 = x + y.
Because x = y + 6, 330 = y + 6 + y, which simplifies to 330 = 2y + 6.
Now all we need to do is simplify the equation. First, we subtract 6 from both sides:
330 - 6 = 324
2y + 6 - 6 = 2y.
So we have 324 = 2y. Then we divide both sides by 2 to get:
162 = y
Plug in y = 162 into the equation x = y + 6 to get:
x = 162 + 6
x = 168
Let's check to make sure our answer is right. 168 is 6 more than 162. 162 + 168 equals 330. So our two numbers are 168 and 162.
Answer:
y=3x.........1
y=x^2-10.......2
substituting value of eq 1 to 2
3x=x^2-10
x^2-10-3x=0
x^2-3x-10=0
x^2-5x+2x-10=0
X(x-5)+2(x-5)=0
(x-5)(X+2)=0
then
X=5 or X=-2
again
y=??
when X=5
y=3×5=15
when X=-2
y=-6
Answer:
it’s b :)
Step-by-step explanation:
Answer is D. for every 1 small mouth caught, it is estimated you will catch 3 largemouth bass
By collecting like terms we have: